2022
DOI: 10.1161/strokeaha.121.035296
|View full text |Cite
|
Sign up to set email alerts
|

Angiographic and Hemodynamic Features in Asymptomatic Hemispheres of Patients With Moyamoya Disease

Abstract: Background and Purpose: There is also a risk of stroke in the asymptomatic hemispheres of moyamoya disease (MMD), but it does not draw enough attention. The study investigated the differences between the three types of asymptomatic hemispheres in MMD and their associations with the two types of symptomatic hemispheres, respectively. Methods: Retrospectively reviewed clinical and imaging characteristics of asymptomatic and symptomatic hemispheres in cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Identifying the brain volume, which is an important component of brain structure ( Salinas et al, 2021 ), as well as angiographic features is an essential part of the research on MMD, as it can provide further information about the pathogenesis and neuropathology of the disease ( Kazumata et al, 2019 , 2020 ; Tahedl, 2020 ; Sun et al, 2022 ). However, previous studies have focused primarily on the symptomatic hemisphere.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Identifying the brain volume, which is an important component of brain structure ( Salinas et al, 2021 ), as well as angiographic features is an essential part of the research on MMD, as it can provide further information about the pathogenesis and neuropathology of the disease ( Kazumata et al, 2019 , 2020 ; Tahedl, 2020 ; Sun et al, 2022 ). However, previous studies have focused primarily on the symptomatic hemisphere.…”
Section: Discussionmentioning
confidence: 99%
“…According to the clinical presentations and radiological findings, the included MMD patients were divided into ischemic group, hemorrhagic group, and asymptomatic group (without neurological symptoms or only with mild and unspecific symptoms such as headache or dizziness, and with negative findings on MR images). Their hemispheres were classified into five types proposed by Sun et al (2022) : ischemic hemisphere (i-hemisphere), hemorrhagic hemisphere (h-hemisphere), contralateral asymptomatic hemisphere of i-hemisphere (ai-hemisphere), contralateral asymptomatic hemisphere of h-hemisphere (ah-hemisphere), and bilateral asymptomatic hemispheres in asymptomatic group (aa-hemisphere) ( Figure 1 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…They concluded that asymptomatic patients had less advanced Suzuki's angiographic stage and lower degree of hemodynamic failure than the others. 28 However, they did not evaluate the development of periventricular anastomosis such as choroidal anastomosis, which is recognized as very important factors to cause cerebrovascular events in moyamoya disease. [21][22][23] In addition, this study demonstrated that the microbleeds was another predictor for hemorrhagic stroke in asymptomatic moyamoya disease.…”
Section: Stroke Risk and Predictors In Asymptomatic Moyamoya Diseasementioning
confidence: 99%
“…However, as previously reported, cerebral hemodynamics is not always normal even if the disease is superficially silent, and cerebral hemodynamics may be taken into consideration when deciding on a future treatment plan. 11,28 Finally, we did not perform the genetic testing for RNF213 mutations in this study, because in 2012, when this study was started, it was not so common to test for RNF213 mutations in any hospital as it is today. Further studies on the impact of RNF213 mutations on the phenotype and outcome in asymptomatic moyamoya disease should be considered in the future.…”
Section: Stroke Risk and Predictors In Asymptomatic Moyamoya Diseasementioning
confidence: 99%